Contribution of individual PKC isoforms to breast cancer progression - Urtreger, Alejandro Jorge (2012)
The protein kinase C (PKC) family of serine/threonine kinases has been intensively studied in cancer since their discovery as major receptors for the tumor-promoting phorbol esters. The contribution of each individual PKC isozyme to malignant transformation is only partially understood, but it is clear that each PKC plays different role in cancer progression. PKC deregulation is a common phenomenon observed in breast cancer, and PKC expression and localization are usually dynamically regulated during mammary gland differentiation and involution. In fact, the overexpression of several PKCs has been reported in malignant human breast tissue and breast cancer cell lines. In this review, we summarize the knowledge available on the specific roles of PKC isoforms in the development, progression, and metastatic dissemination of mammary cancer. We also discuss the role of PKC isoforms as therapeutic targets, and their potential as markers for prognosis or treatment response.